Deubiquitinating Enzymes Regulate Skeletal Muscle Mitochondrial Quality Control and Insulin Sensitivity in Patients With Type 2 Diabetes - Wagner S. Dantas; Elizabeth C. Heintz; Elizabeth R. M. Zunica; Jacob T. Mey; Melissa L. Erickson; Kathryn P. Belmont; Analisa L. Taylor; Gangarao Davuluri; Hisashi Fujioka; Ciarán E. Fealy; Charles L. Hoppel; Christopher L. Axelrod; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Activation of mitochondrial fission and quality control occur early in the onset of insulin resistance in human skeletal muscle. We hypothesized that differences in mitochondrial dynamics, structure and bioenergetics in humans would explain the onset and progression of type 2 diabetes (T2D). Methods Fifty‐eight sedentary adults (37 ± 12 years) were enrolled into one of three groups: (1) healthy weight (HW), (2) overweight and obesity (Ow/Ob), or (3) T2D. Body composition, aerobic capacity, and insulin sensitivity were assessed during a 3‐day inpatient stay. A fasted skeletal muscle biopsy was obtained to assess mitochondrial functions. C2C12 myoblasts were transfected with FLAG‐HA‐USP15 and FLAG‐HA‐USP30 and harvested to assess mitochondrial dynamics and cellular insulin action. Results Insulin sensitivity and aerobic capacity were lower in Ow/Ob (132% and 28%, respectively) and T2D (1024% and 83%, respectively) relative to HW. Patients with T2D presented with elevated skeletal muscle mitochondrial fission (3.2 fold relative to HW and Ow/Ob), decreased fusion, and impairments in quality control. Mitochondrial content was lower in Ow/Ob (26%) and T2D (56%). USP13 (84%), USP15 (96%) and USP30 (53%) expression were increased with decreased Parkin and Ub activation in T2D alone. USP15 (R2 = 0.55, p < 0.0001) and USP30 (R2 = 0.40, p < 0.0001) expression negatively correlated with peripheral insulin sensitivity. USP15 and USP30 overexpression activated DRP1 (3.6 and 3.7 fold, respectively) while inhibiting AKT (96% and 81%, respectively) and AS160 (2.1 and 3.5 fold, respectively) phosphorylation. Conclusion Mitochondrial fragmentation bypasses defects in mitophagy to sustain skeletal muscle quality control in patients with T2D.